LEPscO: Mathematical literacy learning environment for the Guru Penggerak program - Gustiningsi, Tria; Putri, Ratu Ilma Indra; Zulkardi; Hapizah (Journal on Mathematics Education, 2024)
Mathematical literacy stands as a critical skill imperative for navigating the complexities of the 21st century. Enhancing students' mathematical literacy necessitates comprehensive engagement across the educational landscape. This aligns with the Guru Penggerak (GP) initiative, established by the government to serve as educational leaders, propelling the entire educational system forward. Nonetheless, the current GP program needs more specific provisions addressing mathematical literacy, and the existing learning environments for mathematical literacy remain constrained. Consequently, there is a pressing need to develop a dedicated mathematical literacy learning environment within the GP framework. This study endeavors to create a mathematically literate learning environment that is both valid and practical, potentially impacting the GP program significantly. Employing a design research approach, the study progresses through three key stages: preliminary, prototyping, and assessment. Seven teachers participated as subjects, using data collection methodologies including walkthroughs, observations, questionnaires, and interviews, which were analyzed descriptively. Findings indicate the development of a model for a mathematical literacy learning environment termed D-C-C with the LEPscO framework, which is deemed valid due to its alignment with the PISA framework, Indonesian educational curriculum, and unambiguous language. Moreover, the model proves practical for implementation within the GP program, exhibiting potential effects such as enhanced teacher satisfaction, learning, organizational support, and utilization of new knowledge, alongside improved student outcomes reflecting heightened mathematical literacy proficiency. This research contributes to educational discourse by introducing the LEPscO Framework, encompassing a Digital-Class-Community learning environment, structured learning processes encompassing training, classroom implementation, knowledge sharing, and community development, and targeted learning outcomes focusing on teachers' comprehension and reinforcement of mathematical literacy in education.